2008
DOI: 10.1051/forest:2008009
|View full text |Cite
|
Sign up to set email alerts
|

Thinning intensity and growth response in SW-European Scots pine stands

Abstract: -The effect of different thinning intensities on growth and yield was studied in Pinus sylvestris L. stands at the south-western limit of its distribution area (Central Spain), using five long-term thinning trials. Data were analysed collectively considering several factors (trial, block, plot and period) as random effects. Total volume and volume increment decreased with thinning intensity, this loss being more significant in the case of moderate and heavy thinning. No difference was found among treatments fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 26 publications
5
31
1
Order By: Relevance
“…This can be explained by the fact that, in order to obtain a remaining stand of 400 trees per hectare, a greater amount of basal area must be removed from the higher productivity stands due to the larger size of the trees. Even though the basal area values for the thinned areas are close to those for the unthinned ones, the former most likely will not pass the latter, confirming the results obtained in several thinning studies carried out by Hasenauer et al (1997), Simard et al (2004), Río et al (2008), andSkovsgaard (2009). This statement can only be confirmed after the study plots undergo the first commercial thinning operation, allowing the modeling of post-thinning growth.…”
Section: Error Sourcesupporting
confidence: 63%
“…This can be explained by the fact that, in order to obtain a remaining stand of 400 trees per hectare, a greater amount of basal area must be removed from the higher productivity stands due to the larger size of the trees. Even though the basal area values for the thinned areas are close to those for the unthinned ones, the former most likely will not pass the latter, confirming the results obtained in several thinning studies carried out by Hasenauer et al (1997), Simard et al (2004), Río et al (2008), andSkovsgaard (2009). This statement can only be confirmed after the study plots undergo the first commercial thinning operation, allowing the modeling of post-thinning growth.…”
Section: Error Sourcesupporting
confidence: 63%
“…Primicia et al (2013) also found a weak and temporary effect of the first thinning on the tree ring width of dominant and codominant pines in the same study site. Although thinning from below in Scots pine stands appears to particularly enhance the growth of intermediate trees (Río et al, 2008), we observed that the biggest trees (DBH comprised between Q 50 and Q 100 ) were the most responsive ones to the first thinning. In the study site, the initial stand structure of Scots pine was greatly variable among plots (lower pine density with higher quadratic mean diameter, higher tree and stand volume in unthinned than in thinned plots).…”
Section: Discussionmentioning
confidence: 62%
“…In the thinned plots, the yield reduction by thinning is counteracted by the enhancement of individual tree growth, resulting in lower stand density but bigger tree size. However, a reduction in either stand or merchantable volume and stand growth has been frequently observed following moderate to very heavy thinning, although it was also absent after light thinning or in control plots in other Scots pine stands few years after thinning Mäkinen & Isomäki, 2004;Mäkinen et al, 2005;Río et al, 2008;Crecente-Campo et al, 2009). …”
Section: Influence Of Thinning Intensity and Canopy Type On Scots Pinmentioning
confidence: 99%
See 1 more Smart Citation
“…nc: off-site carbon stock was not reported by the authors 2004; Río et al, 2008b) and of carbon stocks in the Mediterranean region (Bravo-Oviedo et al, 2015;RuizPeinado et al, 2016).…”
Section: Silvicultural Options Thinningmentioning
confidence: 99%